EFFECTIVENESS OF THE LARVACIDE ETHANOL EXTRACT OF SOURSOP (Annona muricata L.) LEAVES AGAINST Aedes aegypti LARVA - Selvi Marcellia; Tiara Inggrit Margareta; Agustina Retnaningsih (Universitas Airlangga, Surabaya, Indonesia, 2024)
Highlights Dengue fever, caused by mosquitoes known as Aedes aegypti, can be avoided by applying larvicides while the insects are still in their larval stage. The extract from soursop leaves at a concentration of 3% is the most effective for Aedes aegypti larvae, resulting in 100% mortality. Abstract Background: Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by one of the four serotypes of dengue virus transmitted through mosquitoes, especially Aedes aegypti and Aedes albopictus. As the Aedes aegypti mosquito-borne DHF illness is still in its larval stage, it can be prevented by utilizing larvicides. A more secure and efficient method to eliminate mosquitoes is by using natural larvicides. Underutilized soursop leaves contain secondary metabolite components that can potentially be larvicides, such as annonins, saponins, flavonoids, and tannins. Objective: This study was to determine the effectiveness of soursop leaf extract as a larvicide in controlling Aedes aegypti vectors and to determine the most effective concentration of soursop leaf extract as an Aedes aegypti larvicide. Material and Method: The study was an analytic observational study utilizing a cross-sectional methodology. This study was carried out from March to May 2022. Soursop leaves were extracted using the percolation method, employing a solvent of 96% ethanol with alkaloids, flavonoids, saponins, and tannins. Results: The soursop leaves extract yielded in this study was as much as 131.22 grams (13.12%). The most effective concentration of soursop (Annona muricata L.) leaves was 3%, with a mortality value of 100%, not much different from the value resulting from 1% temephos. The LC50 results obtained a value of 0.163%. Conclusion: Soursop leaf extract was effective as a larvicide against Aedes aegypti mosquito larvae.